Digital signal processing method based on Maxi-Mini distance algorithm. (1st July 2010) - Shaaban, Noha
A fast digital signal processing method for numerical analysis of individual signals from CdZnTe compound semiconductor detectors is introduced in this paper. Using Maximum-Minimum (Maxi-Mini) Distance Algorithm, a parametric approach has been used for classifying the waveforms into a set of clusters, each has a similar signal shape with a corresponding pulse height spectrum. A corrected total pulse height spectrum was obtained by applying a normalisation factor for the full-energy peak for each cluster with much improvement in the energy spectrum characteristics. This method is applied successfully for a real measured data and can be applied to any detector that suffers from signal shape variation.